Physiologic Basis of Symptoms in Pleural Disease - DeBiasi, Erin M.; Feller-Kopman, David (Seminars in Respiratory and Critical Care Medicine, 2019)
Pleural effusions are commonly encountered and have a significant impact on the respiratory system. The reported effect of thoracentesis on physiologic parameters including oxygenation, lung volumes, and respiratory mechanics is variable likely owing to studies with a small, heterogeneous population of patients.Most patients who are short of breath from pleural effusion experience relief following drainage due to improvement in the length–tension relationship of the respiratory muscles. An observed increase in oxygenation following thoracentesis is likely due to improved ventilation and perfusion matching. Recent advances in methods of measuring pleural pressure provide a greater understanding of the impact of pleural effusion on pleural pressure and changes in pleural pressure with thoracentesis; however, there has been no demonstrated benefit of routine monitoring of pleural pressure to reduce complications from thoracentesis. Manometry does allow for the identification of patients with unexpandable lung which is useful when determining options for pleural palliation. The following article will review the pathophysiological effects of pleural effusion and thoracentesis.
Keywords: pleural effusion; dyspnea; thoracentesis; pleural manometry